Inspired by Nature: Facile Design of Nanoclay–Organic Hydrogel Bone Sealant with Multifunctional Properties for Robust Bone Regeneration. (2nd September 2020) - Lee, Chung‐Sung; Hwang, Hee Sook; Kim, Soyon; Fan, Jiabing; Aghaloo, Tara; Lee, Min
Abstract: Bone repair is a complex process involving the sophisticated interplay of osteogenic stem cells, extracellular matrix, and osteoinductive factors, and it is affected by bacterial toxins and oxidative stress. Inspired by the nature of plant‐derived phytochemicals and inorganic–organic analogues of the bone extracellular matrix, herein, the facile design of a nanoclay–organic hydrogel bone sealant (NoBS) that integrates multiple physicochemical cues for bone regeneration into a single system is reported. Assembly of phytochemical‐modified organic chitosan and silica‐rich inorganic nanoclay serves as highly biocompatible and osteoconductive extracellular matrix mimics. The decorated phytochemical exerts inherent bactericidal and antioxidant activities, and acts as an intermolecular networking precursor for gelation with injectable and self‐healing capabilities. Moreover, the NoBS exerts osteoinductive effects mediated by the nanoclay, which regulates the Wnt/ b ‐catenin pathway, along with the addition of osteoinductive signals, resulting in bone regeneration in a nonhealing cranial defect. Engineering of this integrated bone graft substitute with multifunctional properties inspired by natural materials may suggest a promising and effective approach for creating a favorable microenvironment for optimal bone healing. Abstract : A nature‐inspired nanoclay–organic hydrogel bone sealant is developed by coassembly of inorganic nanoclay and organic phytochemical‐reinforced chitosan, thereby mimicking the plant and bone microenvironment. The system serves as a biocompatible and osteoconductive microenvironment with multiple desirable physicochemical properties, including self‐healing and antibacterial and antioxidant activities, for robust bone repair in a single system.